Association of polycyclic aromatic hydrocarbons metabolites and risk of diabetes in coke oven workers. (April 2017) - Yang, Liangle; Yan, Kai; Zeng, Dan; Lai, Xuefeng; Chen, Xuguang; Fang, Qin; Guo, Huan; Wu, Tangchun; Zhang, Xiaomin
Abstract: Elevated polycyclic aromatic hydrocarbons (PAHs) metabolites have recently been linked to increased risk of diabetes in the general population, but little is known about the risk of diabetes due to high pollution levels of PAHs exposure. We aimed to examine whether occupational exposure to PAHs would be one of the important risk factors for diabetes in the coke oven workers. A total of 1472 coke oven workers with complete data were qualified for the present study. We measured 12 urinary monohydroxy polycyclic aromatic hydrocarbons (OH-PAHs) by gas chromatography–mass spectrometry (GC-MS). Multiple logistic regression was used to evaluate the associations between urinary OH-PAHs and risk of diabetes, with adjustment for the potential confounders. We found that elevated urinary 4-hydroxyphenanthrene (4-OHPh) was significantly associated, in a dose-dependent manner, with increased risk of diabetes ( P trend  = 0.003). Compared with individuals with 4-OHPh in the lowest quartile, the adjusted odds ratio (OR) of diabetes among those in the highest quartile was 2.80 (95% CI = 1.37–5.71). In stratified analysis, the association was more prominent in those who were smokers, overweight (BMI ≥24 kg/m 2 ), with longer working years (≥20 years) and worked at coke oven settings. In addition, high levels of 4-OHPh combined with longer working years or overweight had a joint effect on the risk of diabetes. Our data suggested that elevated 4-OHPh was dose-responsive associated with increased risk of diabetes in the coke oven workers. The risk assessment of diabetes related to occupational PAHs exposure should take working years and BMI into consideration. Graphical abstract: Highlights: Occupational exposure to 4-OHPh was dose-dependent related to diabetes. The association was modified by lifestyle and occupational factors. Joint effects of 4-OHPh exposure with working years or BMI on diabetes were observed. Abstract : Elevated 4-OHPh was dose-responsive associated with increased risk of diabetes in the coke oven workers.